Learning from the global financial crisis : creatively, reliably, and sustainably - Shrivastava, Paul; Statler, Matthew (High reliability and crisis management., 2012)
This title is motivated by the simple hope that the cloud of the global financial crisis may yet have a silver lining - that political leaders, economists, and management scholars might seize this opportunity to reflect critically on the assumptions, practices, and infrastructures that have precipitated the crisis and to imagine and create new forms of organization that sustainably enhance the well-being of global stakeholders.